2020
DOI: 10.1371/journal.pone.0229145
|View full text |Cite|
|
Sign up to set email alerts
|

Inactive matrix gla protein plasma levels are associated with peripheral neuropathy in Type 2 diabetes

Abstract: Aims/Hypothesis Diabetic peripheral neuropathy is a frequent and severe complication of diabetes. As Matrixgla-protein (MGP) is expressed in several components of the nervous system and is involved in some neurological disease, MGP could play a role in peripheral nervous system homeostasis. The aim of this study was to evaluate factors associated with sensitive diabetic neuropathy in Type 2 Diabetes, and, in particular, dephospho-uncarboxylated MGP (dp-ucMGP), the inactive form of MGP. Methods 198 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Since dp-ucMGP is a VK-dependent protein, reduced VK status is an independent risk factor for diabetic peripheral neuropathy. Hence, treatment with VK supplements may be a preventive measure in diabetic patients at risk of peripheral neuropathy [142].…”
Section: The Effects Of Vitamin K On Metabolic Disordersmentioning
confidence: 99%
“…Since dp-ucMGP is a VK-dependent protein, reduced VK status is an independent risk factor for diabetic peripheral neuropathy. Hence, treatment with VK supplements may be a preventive measure in diabetic patients at risk of peripheral neuropathy [142].…”
Section: The Effects Of Vitamin K On Metabolic Disordersmentioning
confidence: 99%
“…Other studies found that the accumulation of advanced glycation end products correlated with coronary artery calcification in patients with type 1 DM (T1DM) [ 43 ] and in those with severe aortic valve stenosis [ 40 ]. Furthermore, high ucMGP levels were detected in DM patients and indicated a risk of arterial calcification, which has been observed in non-diabetic subjects [ 44 , 47 ] and T2DM patients [ 44 , 45 , 46 ].…”
Section: Possible Effect Of Vk Supplementation On Insulin Secretiomentioning
confidence: 93%
“…Inactive MGP is identified in its carboxylated or phosphorylated forms, including the uncarboxylated MGP (ucMGP), carboxylated but not phosphorylated MGP (dpcMGP), phosphorylated but uncarboxylated (pucMGP), and the fully inactive uncarboxylated, dephosphorylated MGP (dpucMGP) [ 39 , 40 ]. Several studies have described that medial calcification is observed in DM patients, which correlates with the presence of VKDPs [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. An early report indicated that media calcification was higher in DM patients than in the non-diabetic population [ 42 ].…”
Section: Possible Effect Of Vk Supplementation On Insulin Secretiomentioning
confidence: 99%
See 2 more Smart Citations